How does mitochondria function contribute to aerobic performance enhancement in lizards? - Reardon, Kara M.; Walton, Brenna N.; Husak, Jerry F. (Frontiers in Physiology, 2023)
Aims: Aerobic exercise typically enhances endurance across vertebrates so that chronically high energy demands can be met. Some known mechanisms of doing this include increases in red blood cell numbers, angiogenesis, muscle fiber adaptions, mitochondria biogenesis, and changes to cellular metabolism and oxidative phosphorylation. We used green anole lizards (Anolis carolinensis) to test for an effect of aerobic exercise on metabolism, mitochondria densities, and mitochondrial function. Methods: We first tested the response of green anoles to endurance training and pyrroloquinoline quinone (PQQ) supplementation, which has been shown to increase mitochondria biogenesis. In a second experiment, aerobic exercise increased endurance and decreased resting metabolic rate (RMR) in both male and female green anoles. Results: Aerobic exercise led to increased endurance and decreased standard metabolic rate (SMR), while PQQ did not affect endurance and increased SMR. Higher counts of mitochondrial gene copies in trained lizards suggested additional mitochondria adaptations to achieve increased endurance and decreased metabolism. A mitochondrial stress test revealed no effect on baseline oxygen consumption rates of muscle fibers, but untrained lizards had higher maximal oxygen consumption rates with the addition of metabolic fuel. Conclusions: It is likely that trained lizards exhibited lower maximal oxygen consumption rates by developing higher mitochondria efficiency. This adaptation allows for high ATP demand to be met by making more ATP per oxygen molecule consumed. On the other hand, it is possible that untrained lizards prioritized limiting reactive oxygen species (ROS) production at rest, while sacrificing higher levels of proton leak and higher oxygen consumption rates when working to meet high ATP demand.